APPLICATION OF SONG VIDEO CLIP MEDIA ON THE MASTERY OF ENGLISH VOCABULARY OF CLASS 7 STUDENTS OF SMP NEGERI 5 TABUKAN UTARA - Walukow, Theovinci Nathanael; Liando, Nihta V. F.; Kumayas, Tirza A. (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Increasing mastery of English vocabulary is important in the context of education in Indonesia. One of the methods used in an effort to improve vocabulary mastery is the application of song video clip media in learning. This research aims to find out whether song video clip media in learning can improve students' vocabulary mastery at SMP Negeri 5 Tabukan Utara. The research method used was pre-experimental research with a one group pretest-posttest design. By implementing or using song video clip media in learning English vocabulary, researchers obtained data that student learning outcomes increased. Based on data analysis, it can be concluded that the use of song video clip media can improve the vocabulary mastery of grade 7 students at SMP Negeri 5 Tabukan Utara. The average pre-test score was 42.57 and post-test was 75.42. From these results, it can be seen that the post test scores are higher than the pre test results, and it can be concluded that the use of song video clip media can improve students' vocabulary mastery.